REAÇÕES LITERÁRIAS À CULTURA DE RECIPROCIDADE DO ANTIGO MUNDO MEDITERRÂNEO: UMA LEITURA DA LINGUAGEM ECONÔMICA DO EVANGELHO DE MATEUS - Lima, Anderson de Oliveira (2014)
This research assumes that the Gospel of Matthew is a literary document produced at the end of the first century CE. in some urban environment of the ancient Mediterranean World, where it differs from the other gospels of the New Testament by economic emphasis in its language, and also by its content. We try to demonstrate the importance of this Matthew s language feature for the development of Gospels discourse, and to understand it, we deal with the approximations between this speech and some socioeconomic models known in the real world of the great urban centers of that time. Along the discussion, we conclude that the author of Matthews Gospel is part of an embracing debate between new judaisms that kept conflictual relations with the Greco-Roman domain and their cultural heritage. Matthew, in particular, rejects the complete ownership of clientelist patterns in interpersonal relations of the disciples of Jesus, while also appropriates the foreign socioeconomic model to develop its religious imaginary. We argue that in Matthew, God takes, as a character, the features of a divine patron who protects and benefits its faithful clients, and in retribution, they should do good deeds for the poor. However, despite this vertical relationship religious be desirable, the gospel rejects other clientelistic ties that rating the human being, and sees them as a betrayal to the first sovereign patron.